Automated technology for verification and analysis : 13th International Symposium, ATVA 2015, Shanghai, China, October 12-15, 2015, Proceedings /: 13th International Symposium, ATVA 2015, Shanghai, China, October 12-15, 2015, Proceedings. (2015) - Unknown
No abstract available